Robotic versus Vaginal Surgery for Treatment of Pelvic Organ Prolapse: A Comprehensive Review - Nikita Alfieri; Giorgia Gaia; Stefano Terzoni; Margarita Afonina; Anna Maria Marconi (Clinical and Experimental Obstetrics & Gynecology)
Objectives: The aim of this study was to compare robotic-assisted surgery (RS) and vaginal surgery (VS) for pelvic organ prolapse (POP) through an updated review. Mechanism: We performed a comprehensive review from March 1, 2022 up to April 1, 2022. All comparative studies that compared RS and VS for the management of POP were included. Findings in Brief: A total of 10 non-randomized studies including 1424 participants were included in the review. The results revealed that robotic surgery (RS) was associated with longer operative time, less estimated blood loss, and fewer postoperative complications. There were no differences between the length of hospital stays, intraoperative complications and effectiveness between the two groups. Conclusions: RS and VS have comparable efficacy, although RS was associated with less blood loss and postoperative complications. The choice of surgical procedure depends on the surgeon’s discretion and the patient’s preference.